Avt.: I.A. Krupenikov, D.A. Mirskij [i] M.M. Radul. Otv. red.: Ja.S. Grosul [i] M.M. Radul (["Mysl'"], 1970)
S bibliogr., ill-mi, krt-mi, tab-mi i ukaz. Sovetskij Sojuz Geografičeskoe opisanie v 22 t.t.